The fibromyalgia bladder index - Brand, K.; Littlejohn, G.; Kristjanson, Linda; Wisniewski, S.; Hassard, T. (Springer UK, 2007)
AB The aim of this study was to determine whether an existing outcome measure, the Interstitial Cystitis Symptom and Problem Index (ICSI/ICPI), is a valid, reliable, and clinically relevant instrument to assess the sensory urinary symptoms in women with fibromyalgia syndrome (FM). Ninety women with American College of Rheumatology 90 FM and who had at least two sensory bladder symptoms participated in the study. All underwent urological screening to exclude lower urinary tract pathology. All participants completed the following: ICSI/ICPI, Fibromyalgia Impact Questionnaire (FIQ), Medical Outcome Study Short Form 36, King's Health Questionnaire (KHQ), and Vulval Symptom Assessment Scale. Assessment was made for internal consistency reliability, test-retest reliability, and concurrent validity. Factor analysis was used to assess the internal structure of the scale. Factor analysis displayed two separate components of symptom and problem combinations as distinct from the original ICSI/ICPI developed for the interstitial cystitis population. The eight items of the index configured differently and formed two subscales of a newly developed Fibromyalgia Bladder Index. The two subscales of this index include the Bladder Urgency and Pain Subscale and the Bladder Frequency and Nocturia Subscale. This index has high internal consistency reliability (Cronbach's alpha coefficient of 0.81), test-retest reliability showing intraclass correlation of 0.85, and high concurrent validity through correlations between the Fibromyalgia Bladder Index and the KHQ (0.735, p = 0.000) and the FIQ (0.433, p = 0.000). This more specific configuration of the ICSI/ICPI better reflects FM bladder symptomatology. The Fibromyalgia Bladder Index is a validated FM-specific instrument that captures information about the sensory bladder symptoms and their impact in this fibromyalgia population. This instrument should allow for better understanding and management of this important fibromyalgia-associated problem.